Highly Transparent, Flexible, and Hydrophobic Polytetrafluoroethylene Thin Film Passivation for ITO/AgPdCu/ITO Multilayer Electrodes. Issue 11 (5th February 2022) - Kim, Seong‐Won; Kang, Chaeyoung; Kim, Han‐Ki
Abstract: Transparent and flexible polytetrafluoroethylene (PTFE) thin film passivation for ITO/AgPdCu (APC)/ITO (IAI) electrodes is developed to prevent severe degradation and maintain the reliable performance of the flexible IAI electrodes. Also, oxygen ion beam treatment (IBT) on the surface of the IAI electrode improves the adhesion between the top ITO and PTFE passivation layer, as well as the performance of the passivation layer. The IAI electrode with PTFE passivation exhibits constant sheet resistance, transmittance, and flexibility, even after the 85 °C and 85% RH test. However, the bare IAI electrode shows a significant increase in sheet resistance and a decrease in transmittance and flexibility, owing to the incorporation of moisture and impurities into the IAI layer, and agglomeration of the APC layer. To demonstrate the feasibility of PTFE passivation, the performance of flexible and transparent thin film heaters (TFHs) with the bare IAI and PTEF/IAI samples are compared. The better stability and reliability of the PTFE/IAI‐based TFHs than the bare IAI‐based TFHs indicate that the PTFE film effectively prevents the introduction of moisture and impurities. The performance of the TFH with PTFE/IAI electrode implies that sputtered PTFE film is a promising transparent and flexible thin film passivation for high‐quality oxide‐metal‐oxide multilayer electrodes. Abstract : The PTFE thin film, which increased adhesion applied O2 –IBT, protects the IAI electrode, confirming that all interfaces of each layer are clearly maintained and no degradation occurs even after the long‐term of 85 °C and 85% RH test. It implies sputtered PTFE film is a promising transparent and flexible thin film passivation for high‐quality oxide‐metal‐oxide multilayer electrodes.